Clinical Response to Apatinib Combined With Brain Radiotherapy in EGFR Wild-Type and ALK-Negative Lung Adenocarcinoma With Multiple Brain Metastases - Ying, Xiaofang; Liu, Huali; Wang, Mingwei; Peng, Min; Ruan, Peng; Verma, Vivek; Han, Guang (Frontiers in Oncology, 2020)
Abstract Background: Brain radiotherapy is the standard treatment option for multiple brain metastases (BMs) from non-small cell lung cancer (NSCLC), especially in the absence of a driver mutation. However, the prognosis for such patients remains poor. Apatinib is a potent antiangiogenic compound directed at the vascular endothelial growth factor receptor-2 (VEGFR-2); however, to date, there are no investigations of apatinib concurrent with brain radiotherapy for NSCLC patients with BMs. We report a case of EGFR wild-type and ALK-negative lung adenocarcinoma patient with multiple symptomatic BMs, who received apatinib together with brain radiation therapy. A favorable oncologic outcome was achieved for both brain metastatic lesions and the primary pulmonary tumor. Case presentation: A 61-year-old female (never smoker) who initially presented with headache and dizziness was diagnosed with lung adenocarcinoma with multiple brain metastasis (cT2aN3M1b stage IV), and was negative for EGFR and ALK. The patient refused to receive chemotherapy and was only amenable to brain radiotherapy and targeted therapy. After approval from the institutional ethics committee, she underwent concurrent oral apatinib (500mg/day) with whole brain radiation therapy (WBRT) (37.5Gy) with simultaneous in-field boost (49.5Gy) in 15 fractions with image guided intensity-modulated radiotherapy. Three weeks later, neurologic symptoms entirely ceased and a partial response (PR) for the BMs with near-complete resolution of peritumoral brain edema was achieved. Chest CT performed at the same time and showed shrinkage of the lung primary with a PR. The patient suffered grade III oral mucositis one week after brain radiotherapy and refused further apatinib. At 12 months after brain radiotherapy, the brain tumors remained well controlled. Conclusions: This is the first known documentation of a rapid clinical response of apatinib concurrent with brain radiotherapy in a lung adenocarcinoma patient with symptomatic multiple BMs. Apatinib combined with brain radiotherapy could be an alternative treatment option for BMs from NSCLC, especially for those without a driver mutation. Further clinical trials are required to corroborate this discovery.